The Effect Of Storage Temperature On The Quality Of Honey - Silvester Maximus Tulandi (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2019)
Honey is natural liquid produced by honey bees. In reality, the quality can be reduced if the storage is not done properly. Diastase enzyme activity is one of the important honey quality parameters. The purpose of this research was to determine the quality of honey that was influenced by storage temperature on the activity of the diastase enzyme using Spectrophotometry method. Samples were obtained from the beekeeping area of East Jakarta. The results showed that, storage temperature greatly affects the quality of honey. Diastase enzyme activity was significantly different in each treatment at storage temeprature (P-Value < 0,05). Honey’s best storage temperature was at room temperature (26oC) compared to hot (50oC) and cold (±5oC) temperatures.